2020
DOI: 10.3390/ijerph17061988
|View full text |Cite
|
Sign up to set email alerts
|

Development of General Exposure Factors for Risk Assessment in Korean Children

Abstract: There has been an increasing need for the risk assessment of external environmental hazards in children because they are more sensitive to hazardous chemical exposure than adults. Therefore, the development of general exposure factors is required for appropriate risk assessment in Korean children. This study aimed to determine the general exposure factors among Korean children aged ≤18 years. We developed the recommended exposure factors across five categories: physiological variables, inhalation rates, food a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Dias and Tchepel [ 41 ] suggested that the spatio-temporal variability of urban air pollution, as well as indoor exposure and time–activity patterns, should be measured to assess exposure at the individual scale. The indoor environment is important, as it represents the environment in which individuals spend approximately 90% of their time [ 42 , 43 , 44 ]. Therefore, indoor air pollution may have a higher explanatory power than its outdoor counterpart in the evaluation of air pollution exposure for a population [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dias and Tchepel [ 41 ] suggested that the spatio-temporal variability of urban air pollution, as well as indoor exposure and time–activity patterns, should be measured to assess exposure at the individual scale. The indoor environment is important, as it represents the environment in which individuals spend approximately 90% of their time [ 42 , 43 , 44 ]. Therefore, indoor air pollution may have a higher explanatory power than its outdoor counterpart in the evaluation of air pollution exposure for a population [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…The population may be classified into a subset of groups based on socio-demographic characteristics and time-activity patterns that produce similar exposure scenarios; this includes pre-school children, school students, housewives, office workers, and the elderly. The pollutant level exposure of the population may be estimated by integrating their exposure scenarios [42,44]. A new methodology was tested in Madrid, Spain to improve the estimation of population dynamics.…”
Section: Exposure Scenario Using Time-activity Patternsmentioning
confidence: 99%
“…Similarly, the population in Korea is divided into different age groups for exposure assessment based on age, physiological status, and consumption patterns. These groups include toddlers (> 2 years; 12.2 kg; 0.41 L/day), children (3-12 years; 26.0 kg; 0.72 L/day), adolescents (13-18 years; 58.2 kg; 0.97 L/day), and adults (≥ 19 years; 62.8 kg; 1.50 L/day), and the data on exposure factors were recently been updated 147,148 . In Japan, adults, both males (64.0 kg) and females (52.7 kg), have relatively low drinking water intake, approximately at 0.67 L/day 149 .…”
Section: Risk Assessmentmentioning
confidence: 99%
“…Exposure factor resources have been developed in Europe [ 5 – 7 ], the United States [ 2 ], Canada [ 8 ], Australia [ 9 ], China [ 10 ], Japan [ 11 ], and Korea [ 12 , 13 ]. Synchronizing and integrating exposure factors across countries is necessary to develop standardized methodologies and protocols for collecting and analyzing data while respecting the inherent variability of exposure factors and characterizing the variability and uncertainty of these data [ 14 ].…”
Section: Introductionmentioning
confidence: 99%